Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Quanta Teknik Gemilang - Darmadi Darmadi; N lilis Suyani; Iman Syatoto; Surya Budiman; Priehadi Dhasa Eka (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research was conducted with the aim to determine the effect of motivation and work discipline on employee performance at PT. ISS Indonesia Placement of Grand Slipi Tower, West Jakarta. This study uses a descriptive associative method with a quantitative approach that is used to test population parameters through statistics. The population in this study are employees who work at PT. ISS Indonesia Placement of the Grand Slipi Tower West Jakarta as many as 60 people using saturated sampling technique. Data collection techniques were carried out using primary data collection methods (observations and questionnaires), secondary data and technical data analysis using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis tests, correlation coefficient analysis, analysis of the coefficient of determination, T test, F test. The results showed that the coefficient of determination of the motivation variable was 55.7% with a correlation coefficient of 0.746, which means that motivation has a strong relationship with employee performance. Hypothesis testing obtained tcount > ttable (4.365 > 2.003), this is also reinforced by a significance value of 0.000 < 0.05. Then H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between motivation on employee performance. The value of the coefficient of determination for the work discipline variable is 58.7% with a correlation coefficient of 0.766, which means that work discipline has a strong relationship with employee performance. Testing the hypothesis obtained the value of tcount > ttable (4.937 > 2.003), this is also strengthened by a significance value of 0.000 <0.05. Then H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between work discipline on employee performance. Motivation and work discipline simultaneously have a positive and significant effect on employee performance with the multiple linear regression equation Y = -5.443 + 0.524X1 + 0.550X2 and the coefficient of determination contributes 69.5% while the remaining 30.5% is influenced by other factors not examined in this study. Hypothesis test obtained value Fcount > Ftable (61.384 > 3.16), this is reinforced by a significance value of 0.000 <0.05. So H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between motivation and work discipline together (simultaneously) on the performance of PT. ISS Indonesia Placement of Grand Slipi Tower, West Jakarta